Youtube headlines as copywriting: An interpersonal meaning analysis of ||Superwoman||’s - Dennissa Aulia Adiesti; Iwa Lukmana; Riesky Riesky (Passage, 2020)
YouTube is one of the most influential video-based platforms nowadays. This platform has become the source of living for many people, especially the youth. Apparently, one of the considerations for people to click a video on YouTube is its attractive headline. Therefore this study aims to investigate the interpersonal meaning of the headlines through the use of speech function and its typicality and the realization of the speech function across different types of headline. This study employs a qualitative descriptive design with the help of simple descriptive statistics. The data include 240 headlines of the highest, in-between, and the lowest views videos collected from ||Superwoman|| YouTube channel. These headlines are categorized based on the speech function and its typicality proposed by Halliday (1994) to see the realization of interpersonal meaning. The data are also classified by using the theory of headline types by Maslen (2010). It is found that there are three initiating speech functions realized in the headlines: statement, command, and question. The dominant speech function is statement which is realized typically in a declarative mood. It also shows that statement that arouses curiosity is the most desirable type of headline. The findings indicate equal status between the YouTuber and the viewers through the typical realization of statement, and also signify that viewers are most likely to click a video with a headline that arouses their curiosity. Consequently, the videos can get vast numbers of viewers.Keywords: Headline types, Interpersonal meaning, Speech function, Typicality, YouTube